Changes in composition and pore space of sand rocks in the oil water contact zone (section YU[1] {3-4}, Klyuchevskaya area, Tomsk region); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Nedolivko N. M. Nataliya Mikhailovna (Latest Research in Reservoir Engineering, 2016)
Title screen